Synchronous occurrence of hepatocellular carcinoma and intrahepatic cholangiocarcinoma in both lobes of the liver - Topaloğlu, Serdar; Sağlam, Kutay; Çalık, Adnan; Cobanoğlu, Ümit; Öztürk, Mehmet Halil (Turkish Journal of Gastroenterology, 2014)
Abstract Occurrence of synchronous double primary liver cancer is a very rare condition. A 48-year-old man underwent lateral sectorectomy and tumor resection from segment (S) 7 and S5 for 3 separate liver tumors. Pathological examination revealed intrahepatic cholangiocarcinoma (ICC) in the lateral sector and hepatocellular carcinoma (HCC) in S7 and S5. This report presents the second case in the literature describing the resection of synchronous double cancers of HCC and ICC localized in both lobes of the liver. We also reviewed the clinical and pathological aspects of this coincidental situation.